THE EFFECT OFCURCUMIN PELLET ENRICHED WITH DIFFERENT DOSES ON RED BLOOD OF Pangasius hypophthalmus PROFILE - Hanna Pardede; Iesje Lukistyowati; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstrak This research was conducted on June until October 2018 in Experimental Pond and Laboraty of Parasites and Fish Diseases, Faculty of Fish and Marine Science, University of Riau, Pekanbaru. The purpose of this study was to determine the effect of feeding containing curcumin extract with different doses on the image of red blood in siam jambal fish Pangasius hypophthalmus. The method used is the used in the experimental method with a Cumpletely Randomized Design (CDR) with one factor and 4 treatment . the namely: P0 (Feedingwithout addition of turmeric curcumin extract), P1 (Addition curcumin extract from turmeric in feed at a dose of 0,5 g/kg), P2 Addition curcumin extract from turmeric in feed ar a dose of 0,7 g/kg), P3 (Addition of curcumin extract extract from turmetric in feed at a dose of 0,9 g/kg). The test fish used was Pangasius hypophthalmus with a size was 7-8 cm as many as 600 fishs. The parameters measured are; total erythrocytes, haemaglobin, haematocrit, absolute weight growth, survival rate and water quality measurements. The resullts that the effect of giving curcumin extract from turmeric in feed with the best dose is 0,9 g/kg, which is indicated by a total erythrocyte of 2,91x106 cells/mm3, haemaglobin 10 g/dL , haematocrit 38,33%, absolute weight growth 32 % and survival rate 99,33%. Keywords:Pangasius hypophthalmus,Curcumin extract, Erythrocyte